Vinculin is required for cell polarization, migration, and extracellular matrix remodeling in 3D collagen. Issue 11 (20th July 2015) - Thievessen, Ingo; Fakhri, Nikta; Steinwachs, Julian; Kraus, Viola; McIsaac, R. Scott; Gao, Liang; Chen, Bi‐Chang; Baird, Michelle A.; Davidson, Michael W.; Betzig, Eric; Oldenbourg, Rudolf; Waterman, Clare M.; et al.
ABSTRACT: Vinculin is filamentous (F)‐actin‐binding protein enriched in integrin‐based adhesions to the extracellular matrix (ECM). Whereas studies in 2‐dimensional (2D) tissue culture models have suggested that vinculin negatively regulates cell migration by promoting cytoskeleton‐ECM coupling to strengthen and stabilize adhesions, its role in regulating cell migration in more physiologic, 3‐dimensional (3D) environments is unclear. To address the role of vinculin in 3D cell migration, we analyzed the morphodynamics, migration, and ECM remodeling of primary murine embryonic fibroblasts (MEFs) with cre/loxP‐mediated vinculin gene disruption in 3D collagen I cultures. We found that vinculin promoted 3D cell migration by increasing directional persistence. Vinculin was necessary for persistent cell protrusion, cell elongation, and stable cell orientation in 3D collagen, but was dispensable for lamellipodia formation, suggesting that vinculin‐mediated cell adhesion to the ECM is needed to convert actin‐based cell protrusion into persistent cell shape change and migration. Consistent with this finding, vinculin was necessary for efficient traction force generation in 3D collagen without affecting myosin II activity and promoted 3D collagen fiber alignment and macroscopical gel contraction. Our results suggest that vinculin promotes directionally persistent cell migration and tension‐dependent ECM remodeling in complex 3D environments by increasing cell‐ECM adhesion and traction force generation.—Thievessen, I., Fakhri, N., Steinwachs, J., Kraus, V., McIsaac, R. S., Gao, L., Chen, B.‐C., Baird, M. A., Davidson, M. W., Betzig, E., Oldenbourg, R., Waterman, C., M., Fabry, B. Vinculin is required for cell polarization, migration, and extracellular matrix remodeling in 3D collagen. FASEB J. 29, 4555‐4567 (2015). www.fasebj.org